Analyzing Microbes Manual of Molecular Biology Techniques - Arora, Dilip Kumar; Das, Surajit; Sukumar, Mesapogu; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This Springer Protocols manual is a practical guide to the application of key molecular biology techniques in microbiological research. The focus is on experimental protocols, which are presented in an easy-to-follow way, as step-by-step procedures for direct use in the laboratory. Notes on how to successfully apply the procedures are included, as well as recommendations regarding materials and suppliers. In addition to the practical protocols, important background information and representative results of experiments using the described methods are presented. Researchers in all areas applying microbial systems, such as in molecular biology, genetics, pathology, and agricultural research will find this work of great value.
Microbial DNA extraction, purification and quantitation -- Fluorescent based detection, quantitation and expression of wviral gene by qRT-PCR -- Restriction enzymes and their role in microbiology -- Genetic fingerprinting techniques  for molecular characterization of microbes -- Agarose gel electrophoresis and Polyacrylamide agarose gel electrophoresis: Methods and principles -- Molecular identification of microbes -- Preservation and maintenance of microbial cultures -- Microbes from extreme environment: Molecular identification procedures -- ELISA based identification and detection of microbes -- Analysis of microbial diversity and construction of metagenomic library -- Bioinformatics tools for interpretation of data used in molecular identification -- Molecular phylogenetics of microbes -- Microarray technology: Basic concept, protocols and applications -- Microarray analysis of different functional genes of microorganisms -- DNA cloning and sequencing -- Biological sequence analysis: Algorithms and statistical methods.
Keywords: Microbiology; Medical microbiology; Biochemistry; Microbiology; Medical Microbiology; Biochemistry, general